Blockchain Financial Identity for Inclusive Access in Developing Nations - Sutama Wisnu Dyatmika; Untung Rahardja; Muhtarom Muhtarom; Dwi Nur Ramadhan; Po Abbas Sunarya; Lily Maria Evans (Pandawan, 2026)
The absence of formal financial identity remains a significant barrier to financial inclusion in developing nations, limiting access to essential financial services. Traditional centralized identity systems are often vulnerable to data breaches, fraud, and institutional control, resulting in low public trust. This study aims to explore how blockchain-based identity systems, particularly through the concept of Self-Sovereign Identity (SSI), can address these limitations. The research adopts a qualitative case study approach by analyzing multiple blockchain-based digital identity initiatives across developing regions. The findings reveal that blockchain-enabled SSI enhances data security, transparency, and user autonomy, while improving accessibility to financial services. The key contribution of this study lies in identifying the integration of decentralized identity frameworks as a sustainable solution to strengthen financial inclusion and institutional trust. However, challenges such as infrastructure limitations, scalability issues, and regulatory uncertainty remain critical barriers. This study provides both theoretical insights and practical implications for policymakers, developers, and financial institutions in implementing secure and inclusive digital identity systems.